The evaluation of the programs of gender-responsive school in Yogyakarta - Sudrajat, Sudrajat; Saliman, Saliman; Supardi, Supardi (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2022)
The research aims to evaluate the implementation of the gender-responsive school program in Yogyakarta. It is a descriptive evaluation using the CIPP (Context, Input, Process, Product) model involving the principal, head of the gender-responsive school program, teachers, employees, and students as the subjects. Data were collected by (1) interviews with principals, teachers, heads of gender-responsive school programs, and students; (2) a study of documentation of various educational activities related to the program. Data were analyzed using a qualitative data analysis model by Miles and Huberman consisting of (1) data collection, (2) data reduction, (3) data display, and (4) data verification/conclusion. The research results can be seen from four aspects: (1) the context in implementing gender-responsive school programs refers to various references, including Presidential Instruction No. 9 of 2000, Regulation of the Minister of National Education of the Republic of Indonesia No. 8 of 2008. (2) The inputs for implementing the gender-responsive school program have met the requirements in terms of human resources (teachers and education staff) and the facilities and infrastructure. Most of the teachers already have adequate knowledge about the program's implementation. An integrated team in school management has planned the facilities and infrastructure. (3) Implementing gender-responsive schools is carried out well by developing school culture and organizing activities inside and outside learning. (4) The product of the gender-responsive school program is the formation of conducive school culture, facilities, and infrastructure that ensure the privacy of both male and female students.